Eco-Friendly Packaging: Marketing Sustainability from Product to Delivery - Andi Wardana, Miko; Ardian, Dede; Islam, Fajar (Escalate : Economics and Business Journal, 2024)
This research investigates eco-friendly packaging practices at PT Yakult Indonesia Persada Cab. Padang, focusing on the relationships between packaging materials, marketing communications, perceived environmental impact, and consumer purchase intentions. Employing a quantitative approach, data were collected from 100 consumers using structured surveys and analyzed through Smart PLS. The findings reveal that packaging materials significantly influence consumer perceptions of environmental impact and purchase intentions. While marketing communications were effective in enhancing purchase intentions, their impact on perceived environmental impact was not significant. Furthermore, perceived environmental impact was identified as a crucial mediator between packaging materials and consumer purchasing decisions. These insights underscore the need for PT Yakult to enhance its sustainability strategies and marketing efforts to align with consumer values, thereby fostering brand loyalty and promoting environmental sustainability in West Sumatra.